Designing Engaging Community Learning Application with Children Using Gamification - Zainal Abidin, Norshikin; Baharum, Aslina; Mohd Fairuz Syed Mohd Dardin, Syed; Shahida Ab Fatah, Nur; Ismail, Ismassabah; Moziyana Mohd Yusop, Nurhafizah (International Journal of Engineering and Technology, 2018)
This research presents an approach to engage the children with a learning mobile application. The interest in education and learning process are increasing significantly due to the emerging of digital technologies. The use of e-learning in particularly for children to improve the learning process has been an issue as educators are facing problems on how to promote and to stay engaged with them. Due to the new technology that applies the new method into the e-learning process they able to overcome the problem. The aim of this study is to identify the features and guidelines for designing engaging for community learning with children using gamification technique. Hopefully the proposed community learning application can engage the children using the proposed technique. The research finding revealed that the gamification technique could help the student to engage with the learning material effectively.Â Â